THE EFFECT OF COMBINATION CALCIUM HYDROXIDE-PROPOLIS APPLICATION TO AMOUNT OF NEUTROFIL CELLS ON WISTAR RAT PULP PERFORATION - Ira Widjiastuti; Setyabudi Setyabudi; Nia Nur Haliza (Universitas Airlangga, 2020)
Background: Pulp inflammation can be treated with pulp capping by calcium hydroxide as the gold standard. Pulp capping by calcium hydroxide could causing tissue necrosis followed by inflammation. Calcium hydroxide combined with propolis which have anti-inflammatory effects through inhibition of the Nf-kB pathway and pro-inflammatory cytokines. That process will inhibit the increase of vascular permeability and neutrophil chemotaxis. Inflammatory process can accelerate by controlling the amount of neutrophil cells as a acute phase marker, so the healing process occurs more quickly. Therefore it is necessary to study the amount of neutrophil cells in the pulp perforation of Wistar rats after applicated by combination of calcium hydroxide-propolis. Purpose: To analyze the difference amount of neutrophil cells on the Wistar rats pulp perforation after applicated by calcium hydroxide-propolis combination compared with calcium hydroxide-aquadest Method: M1 tooth perforated for all groups with three types tratment: no medication (control group), calcium hydroxide-aquadest 1: 1 (P-1 group), and calcium hydroxide-propolis 1: 1.5 (P-2 group) and closed with cention. Observations were made on the 1st, and 3rd day with HE staining. Results: One Way ANOVA shown a significant difference (p <0.05) of the average amount of neutrophil cells between all treatment groups on 1st day (p=0,000) and 3rd day (p=0,000). The amount of neutrophil cells in the calcium hydroxide-propolis (P-2) combination group was lower than control group and calcium hydroxide-aquadest (P-1) group on the 1st and 3rd day. Conclusion: The amount of neutrophil cells after application of calcium hydroxide-propolis is lower than calcium hydroxide-aquadest application.